Effect of Rye cover crop on weed control, soybean (Glycine max L.) yield and profitability - Pinnamaneni, Srinivasa Rao; Anapalli, Saseendran S.; Molin, William; Reddy, Krishna N. (Frontiers in Agronomy, 2022)
Abstract: Considerable variations in farm productivity were reported across soils and climates when winter cover crops (CC) were rotated with summer main cash crops. Hence, a three-year field study (2019-2021) was conducted on Dundee silt loam in a humid climate to assess soybean growth and yield, weed control, and profitability under no-till conditions in response to (i) no CC (NC), (ii) winter rye CC rolled when green, followed by soybean planting and desiccation by paraquat (GR) and iii) winter rye CC desiccated using paraquat and rolled followed by soybean planting (BR). Measured leaf area index was comparable among the treatments across the three seasons. The rate of rye CC biomass decay estimated eight weeks after planting (WAP) was much higher than at four WAP. In 2019, at eight WAP plant residue ranged from 29.3% under NC to 52.9% under GR, indicating the paraquat desiccated natural winter vegetation decays faster than the desiccated rye CC biomass. The weed biomass was 72% higher at eight WAP (0.29 Mg ha-1) than that of four WAP (0.17 Mg ha-1) and NC plots had higher weed biomass at both four WAP and eight WAP over CC plots. Field established soybean stand in the GR plots were consistently higher than the NC plots by 8%, 30%, and 22% in 2019, 2020, and 2021, respectively. Soybean yield in NC plot was 13% higher than GR and 15% higher than BR plots in 2019. However, in 2020 and 2021, soybean yield from BR and GR plots was significantly higher than NC plots (10 % and 13%, respectively). In the three-year study, net returns from soybean with rye CC (regardless of GR or BR) in the first year was negative. In the second and third year, net returns in GR and BR were positive and comparable to NC. These results show that a rye CC–based soybean conservation production system could be an economically a viable choice after the first year with an invaluable potential to mitigate climate change through carbon sequestration, weed suppression and positive impact on summer soybean productivity.